CARICOM report - Crawley, Andrew (IDB-INTAL Buenos AiresAR, 2002)
Appraises through detailed analysis, the progress made on integration and CARICOM's contribution to the sustainability of development. Assesses the depth of market integration and functional cooperation by examining the state of policy coordination and harmonization, the level of institutional development and the degree of capacity sharing. Addresses CARICOM's pace of widening and its integration into the world economy, against the backdrop of trends in international trade negotiations.